MODEL PEMBELAJARAN INTERAKSI SOSIAL : EFEKTIVITAS DAN IMPLEMENTASI - noviar, Anggi; Herdiana, Dodi (Journal Of Education, 2024)
Social skills are essential skills that are necessary for success in life, both at school, at work, and in society. Social skills include the ability to communicate, collaborate, solve problems, and adapt. The social interaction learning model is a learning model that emphasizes the interaction between the student and the educator and the student with the other students. Research has shown that social interaction learning models are effective in improving the social skills of pupils. A study conducted by Johnson and Johnson (1999), Suherman (2012), Wulandari (2013), Lestari (2014), Sugiyono (2013), Hamalik (2007), Arsyad (2008), Sa’ud (2011), found that pupils participating in cooperative learning have higher social skills than pupils who do not participate in co-operative learning. To improve the effectiveness of social interaction learning models, educators need to pay attention to some of the following: Educators need to have a good understanding of the theories underlying the learning model of social interaction. Educators should have the necessary skills to manage the classroom effectively. Teachers need to provide support and guidance to learners throughout the learning process. The social interaction learning model is one of the most effective learning approaches to developing the social skills of students. This approach can be applied to a wide range of subjects, both at primary, secondary, and upper school levels.